Sosialisasi dan Edukasi Pasar Modal Syariah sebagai Upaya Meningkatkan Literasi Investasi di Desa Telaga Jernih - Habibah Ramadhani Nasution; Arofiani Mutmainah; Muhammad Yasfin Nasution; Danu Wijaya; M. Amar Adly (Pusat Riset dan Inovasi Nasional, 2026)
This community service program aims to improve public literacy and awareness of the Islamic capital market through socialization and educational activities in Telaga Jernih Village, Secanggang District. Islamic financial literacy in rural areas remains relatively low due to limited access to information and education, leading people to prefer traditional investments such as livestock and plantations. The activity was carried out by the Community Service Program (KKN) team in collaboration with the Indonesia Stock Exchange (IDX) as the main speaker and the village government as a supporting partner. The methods used included observation, counseling, interactive discussions, and simple simulations of Islamic investment practices. The results revealed high enthusiasm among participants, reflected in their active engagement and significant improvement in understanding the concepts, principles, and products of Islamic investment. The community began to realize that Islamic capital market investments are not only halal and safe but also offer long-term economic benefits. This activity positively influenced the community’s mindset to view Islamic financial investment as a complementary form of traditional investment. The program also opened opportunities for forming a village-based Islamic investor community and establishing a financial literacy center as a follow-up initiative. Therefore, this program plays a vital role in strengthening Islamic financial inclusion in rural areas and serves as an initial step toward creating a financially literate, independent, and economically productive society.